Parents Matter: Associations of Parental BMI and Feeding Behaviors With Child BMI in Brazilian Preschool and School-Aged Children - Warkentin, Sarah; Mais, Laís A.; Latorre, Maria do Rosário Dias de Oliveira; Carnell, Susan; Taddei, José Augusto de Aguiar Carrazedo (Frontiers in Nutrition, 2018)
Background: Brazil is undergoing nutritional transition and rates of obesity in preschool and school-aged children are increasing. Excess weight in the first years of life could predict excess weight in adulthood, making it essential to study risk factors in this population. Objective: Our goal was to investigate associations of parent feeding behaviors, as well as more distal familial influences including family SES and maternal and paternal weight, with BMI z-score in preschool and school-aged children in a Brazilian sample. Methods: Cross-sectional study. Data were collected in 14 Brazilian private schools. Parents of children aged 2–8 years (n = 1,071) completed a questionnaire assessing parent feeding behaviors, as well as sociodemographic and anthropometric information. Hierarchical linear regression models were fitted to investigate relationships between parent and child characteristics and child BMI z-score in preschool (2–5 years, n = 397) and school-aged (6–8 years, n = 618) children. Results: Final models indicated that higher maternal BMI and “restriction for weight control” were associated with higher child BMI z-score in both age groups (excessive weight, i.e., BMI ≥ +1 z-score, in preschoolers and school-aged children: 24.4 and 35.9%, respectively). In preschoolers only, “healthy eating guidance” and “pressure” were associated with lower child BMI z-score. For school-aged children, male sex, higher father BMI, and “restriction for health” were associated with higher child BMI z-score. Conclusions: Parent feeding behaviors and parent weight, as well as child sex, are associated with child BMI z-score, with evidence for differential relationships in preschool and school-aged children. Optimal obesity prevention and treatment strategies may differ by child age.